Selective Power Control in Grid-Connected AC Microgrids - Joao Marcus S. Callegari; Lucas S. Araujo; Danilo I. Brandao (IEEE Open Journal of the Industrial Electronics Society)
The increasing penetration of nonlinear loads (NLLs) and distributed energy resources (DERs) in low-voltage grids poses challenges to power quality and grid hosting capacity (GHC). This article proposes a centralized multimode selective power control strategy for grid-connected ac microgrids (MGs) that does not require prior knowledge of MG parameters. The strategy enhances GHC and power quality across multiple MG nodes through coordinated control in two nonsimultaneous modes. In the centralized mode, a generalized power-based control algorithm enables selective harmonic/distortion power dispatch. This formulation improves disturbance rejection and accuracy in point of common coupling (PCC) power tracking. For the first time, feedback, feedforward, and disturbance decoupling actions are applied to distortion/harmonic power in MGs. In the decentralized mode, harmonic current compensation (HCC) is achieved without communication links, reducing data traffic via a selective voltage-detection-based approach. The proposed strategy enables (i) resistive load synthesis at the PCC to damp upstream grid resonances, (ii) sinusoidal current synthesis (SCS) for current quality enhancement and compliance with standards, and (iii) HCC based on voltage measurements to improve voltage quality at internal nodes. Comprehensive simulations evaluate reference tracking, disturbance rejection, grid short-circuit level effects, and mode transitions. Results show that in decentralized mode, PCC voltage THD improved from 10.65% to 1.09% under weak grids. In centralized mode, with SCS up to the 11th harmonic, PCC current THD was reduced from 61.18% to 3.42% under stiff grids. Experimental results confirm the feasibility of implementation in real MGs.